SOFC System Design Using Ideal Efficiency Modeling – Model and Experimental Implementation1. Issue 4 (18th July 2013) - Heddrich, M. P.; Jahn, M.; Michaelis, A.; Näke, R.; Weder, A.
Abstract A simple thermodynamic system model for the analysis and evaluation of possible SOFC system concepts with regard to reachable electric efficiency is presented. All reforming concepts, various available fuels and anode off‐gas recirculation are included in the model. Furthermore, the model allows the characterization of the reforming conditions necessary to reach the calculated and desired electric efficiencies by the use of two dimensionless energy flow ratios, which are introduced. It is presented how to quickly assess system concepts and identify system concepts that are particularly interesting due to a simple process, high electric efficiency, or preferably a combination of those. Within the experimental section, the model is used to support the system design process of a biogas‐driven SOFC system with partial oxidation as reforming concept, without anode off‐gas recirculation. Since adjustable operating parameters are input into the model, the parameters' influence on efficiency and reforming conditions can be analyzed. With the model real system effects are investigated making it possible to reach a maximum gross electric efficiency of 0.55 with the real designed system.